The Importance of Aesthetics as a Dimension in Music Therapy Activity - Bergstroem-Nielsen, Carl (Voices: A World Forum for Music Therapy, 2006)
In Unmoderated Discussions, I began discussing the aesthetic dimension in music therapy, taking Colin Lee's book The Architecture of Aesthetic Music Therapy as a starting-point. Several students and colleagues took part and contributed with further viewpoints, dealing with the positive qualities of the aesthetic dimension for both client and therapist, with the necessary limitation or demarcation of how far the aesthetic view can be taken in music therapy, and with the spiritual (impersonal) aspect of music. Some further thoughts in this article concern the importance of the therapists' musical craft, of musical structure and the theoretical question of what is the nature of the aesthetic dimension. Mention is made of Stige's articles stressing the necessity of applying new concepts that relate the aesthetic dimension to daily life. It is concluded that we need further discussion to clarify the role of the aesthetic dimension in music therapy.